ANALISIS WACANA KRITIS: KONSEP DAN FUNGSINYA BAGI MASYARAKAT - Supriyadi Supriyadi (Universitas Lampung, 2015)
The term of discourse in society has a number of understanding. In this paper discourse is interpreted as an attempt done to dismantle the critically purposes and specific meanings that exist in society beyond the visible discourse. Therefore, this type of discourse called critical discourse. That is, discourse which is critical to disassemble the meaning or intent behind the phenomena or events that developed in the community, such as social issues and political issues that can not be interpreted by conventional discourse analysis. Specifically, the focus of critical discourse lies in the structure of discourse which make, confirm, legitimize, reproduce, or against a relationship of power and domination in society. Meanwhile, its function for the society is to dismantle the abuse practices of power, domination, hegemony, ideology, social class, gender, race, discrimination, interest, reproduction, institutions, social structure, or social order.